Field reports form for submitting seasonal observations of Iowa birds, Mark Proescholdt, summer 2001 - Proescholdt, Market al (2001)
List of birds and locations contributed by Mark Proescholdt. Includes additions to his original summer bird sighting report. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of summer 2001. Epson - sheet feed